Evaluation of the Effect of Intravitreal Bevacizumab (Avastin) in Patients with Diabetic Macular Edema - Mahat, Pawan; Joshi, Purushottam; Pradhan, Eli; Subedi, Prabha (Nepalese Journal of Ophthalmology, 2020)
Introduction: Diabetic macular edema (DME) is the leading cause of visual impairment in patients with diabetes mellitus. The objectives of the study was to figure out the effect of intravitreal injection bevacizumab on visual acuity and retinal thickness in people with DME. Materials and methods: We observed the case records of patients with DME requiring injection Avastin (Genentech Inc., San Francisco, CA, USA) intravitreal from January to July 2016 in Mechi Eye Hospital. The eighty seven eyes of 60 patients with DME were included in the study. Inclusion criteria were determined independently of the age, metabolic control, type of diabetes mellitus, visual acuity, leakage area size,retinal thickness as measured by optical coherence tomography. All the patients were treated with 0.05 ml injection containing 1.25 mg of Avastin (Genentech Inc., San Francisco, CA, USA) after written informed consent. Results: The mean age group was 55.86 ± 9.61 years with 47 males and 13 females. At baseline the median BCVA was 1.00 (0.60-1.30) which improved to 0.78 (0.48- 1.00) at 6 weeks (p=0.001) which further improved to 0.78 (0.48-1.00) Log MAR (p value- 0.005) at 12 weeks and 0.60 (0.43- 1.00) Log MAR at 18 weeks (p value= 0.006). Baseline mean central macular thickness (CMT) on OCT was 436.24 ± 142.2μm which decreased to 387.74±130.98μm at 6 weeks, 346.82 ±116.79 μm at 12 weeks and 307.1 ±105.49μm. Changes in VA and decrease in central subfield macular thickness during follow up visit was statistically significant (p<0.05). Conclusion: In this study, intravitreal injection Avastin resulted in improvement in VA and decrease in retinal thickness in patients with DME.